2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32697
|View full text |Cite
|
Sign up to set email alerts
|

Effects of YouTube Video as Pre-Lecture Preparation

Abstract: is a Network Systems Engineer (FA26A) who has served in various positions across multiple combatant commands. He initially served as a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Only a few studies have reported that some students have rated YouTube videos as less motivating in classrooms [156]. Some authors could not observe a considerable difference in classroom participation [157]. In another study, the authors reported that YouTube may negatively impact the social interaction in the classroom [158].…”
Section: ) Promoting Interest Motivation and Engagementmentioning
confidence: 99%
“…Only a few studies have reported that some students have rated YouTube videos as less motivating in classrooms [156]. Some authors could not observe a considerable difference in classroom participation [157]. In another study, the authors reported that YouTube may negatively impact the social interaction in the classroom [158].…”
Section: ) Promoting Interest Motivation and Engagementmentioning
confidence: 99%
“…For the previous constructs, the categorization was based on theoretical concepts, but for tactics, we found it more useful to create new groups. First, we made a distinction here between using various resources, such as videos [48,66,103,127,167], books [99,167], and hints [47], and techniques, such as memorization [6,139] and note-taking [70,160]. Furthermore, the category of trying includes tactics related to attempting assignments [48,142], solving many problems [7,42], and retaking quizzes [20,162], often tracked with log-file data.…”
Section: 13mentioning
confidence: 99%
“…In contrast to most of the other behavior levels social interactions [19,66,73,96,141,142,157] and collaboration [63,162] are two frequently mentioned tactics. The help category includes asking questions [99,160] and help seeking behavior [69,95], and the preparation category refers to preparing for lectures [167], tests [160], and classes [70,111,171]. Last, the coding category relates to specific tactics used when programming, such as using auto-complete [154], compilation frequency [45,47,154], debugging, and use of version control systems [170].…”
Section: 13mentioning
confidence: 99%
“…See Table 1 for distribution. Further, some majors were more inclined to suggest SIVs for their courses, Architectural Engineering (7), Construction (13) and Mechanical and Aerospace Engineering (7). At least one respondent from these three majors also indicated that general engineering courses should also include SIVs.…”
Section: Resultsmentioning
confidence: 99%
“…Textbook publishers may provide supplemental video content to complement hard-copy or electronic textbooks [5]. Some streaming platforms like YouTube provide opportunities for educational videos [6] and [7]. These platforms offer instructional videos covering general topic overviews to very specific college coursework.…”
Section: Introductionmentioning
confidence: 99%